Breaking isolation: Consciousness-raising as a methodology for academic activism - McCarthy, Lauren; Grosser, Kate (Organization (London, England), 2023)
In this essay we argue that one way to combat the depressing creep of the neoliberal university is to recuperate and re-use consciousness raising (CR) in teaching, administration, research, and engagement. Consciousness-raising can be roughly characterised as first, an apprehending of one’s place in a system, and second, feeling inspired to do something about that system. We propose that CR is an especially helpful way to think about our work in contexts where more structural changes to advance social justice agendas appear to have stalled, or even to have taken a step backwards. There may be potential to co-opt the increasing dominance of individualism in our worlds, by revisiting the role that individual reflection and development plays in social change, as conceptualised within CR. Through examples drawn from our own experiences, we demonstrate how CR happens in our day-to-day interactions, reigniting a sense of meaning in our working lives whilst potentially creating ripples of positive change. We thus call not just for revisiting, but also for reconceptualising and reframing CR rooted in feminist and intersectional praxis as a methodology for academic activism in the contemporary business school.